Measurement and assessment of fidelity and competence in nonspecialist-delivered, evidence-based behavioral and mental health interventions: A systematic review. (September 2022) - Bond, Laura; Simmons, Erik; Sabbath, Erika L.
Abstract: Nonspecialists have increasingly been used to deliver evidence-based, mental health and behavioral interventions in lower resource settings where there is a dearth of specialized providers and a corresponding gap in service delivery. Recent literature acknowledges that nonspecialist-delivered interventions are shown to be effective. However, few studies report on the fidelity (the degree to which an intervention was implemented as intended) and/or competence (general skills of nonspecialists), key concepts that measure quality of evidence-based intervention delivery. This study seeks to understand how both fidelity and competence have been assessed in nonspecialist-delivered, evidence-based interventions with an intended social or psychological behavior-change outcome. Our search results originally yielded 2317 studies, and ultimately, 16 were included in our final analysis. Generally, results from a narrative synthesis indicated that tools used in the studies demonstrated sufficient inter-rater reliability and intra-class correlation components. Included studies used and described a range of fidelity and competence tools. However, the ENhancing Assessment of Common Therapeutic factors tool was the most commonly used tool that measures competence of nonspecialists, and has been adapted to several other settings. The roles of supervisors in mentoring, monitoring, and supervising nonspecialists emerged as a key ingredient for ensuring fidelity. Most studies assessing fidelity were limited by small sample sizes due to low numbers of nonspecialists implementing interventions, however, more advanced statistical methods may not be needed and may actually impede community-based organizations from assessing fidelity data. Our results suggest interventions can share resources, tools, and compare findings regardless with proper supervision. While the two terms "fidelity" and "competence" are often used interchangeably, their differences are noteworthy. Ultimately, both competency and fidelity are critical for delivering evidence-based interventions, and nonspecialists are most effective when they can be evaluated and mentored on both throughout the course of the intervention. Highlights: There is inconsistency in methods, and language in studies assessing the fidelity and competence of nonspecialist providers. Supervision and mentorship play a strong role in fidelity and competence maintenance, improvement, and evaluation. Fidelity and competence assessment is usually conditional on the program being evaluated, but there is room for improvement.